Forced degradation behavior of two-drug combinations: Isolation and characterization of major degradation products by LC-MS - Sversut, Rúbia Adrieli [UNESP]; Vieira, James Cabral; Kassab, Nájla Mohamad; Silva, Denise Brentan; Salgado, Hérida Regina Nunes [UNESP] (My University, 2019)
Oxytetracycline (OTC) belongs to the antimicrobial class, diclofenac sodium (DICLO) and piroxicam (PIRO) are nonsteroidal anti-inflammatory drugs. Fixed-dose combinations of OTC with DICLO or PIRO, available as extended release injectable solutions, are widely indicated for animal use. These drugs were subject to forced degradation (alkaline, acid, neutral, oxidative photolytic conditions) as per ICH Q1 (R2) guideline and the kinetic of degradation reactions was investigated. OTC showed higher degradation under neutral, oxidative, alkaline and acid conditions and DICLO showed extensive photo degradation, while PIRO was the most stable drug under all degradation conditions studied. A total of seven degradation products (DPs) were observed and efficient chromatographic separations of drugs and their DPs were achieved on an InertSustain C8 column using a mobile phase composed by methanol-acetonitrile-water (40:35:25, v/v/v) at pH 2.5, adjusted with formic acid, in isocratic mode. Six DPs were isolated by HPLC-PDA and their chemical structures were proposed based on high resolution MS and MS/MS data. DP 1 to DP 5 had OTC as precursor drug, while DP 6 originated from DICLO photolysis. The chemical structures of DP 1, DP 4 and DP 5 are being reported here for the first time. The HPLC-PDA was adequately validated and it can be used in the quality control routine analysis as stability indicating method for quantification of drugs in pharmaceuticals and evaluation of their accelerated and long-term stability.
Keywords: Forced degradation studies; Kinetic models; Oxytetracycline; Piroxicam; Sodium diclofenac; Stability indicating method